2015
DOI: 10.1016/j.avsg.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Outcomes of Endovascular Procedures for Peripheral Arterial Disease: An Evaluation of California Hospitals, 2005–2009

Abstract: Background Racial/ethnic disparities in treatment outcomes of peripheral arterial disease (PAD) are well documented. Compared to non-Hispanic (NH) whites, blacks and Hispanics are more likely to undergo amputation and less likely to undergo bypass surgery for limb salvage. Endovascular procedures are being increasingly performed as first line of therapy for PAD. In this study, we examined the outcomes of endovascular PAD treatments based on race/ethnicity in a contemporary large population-based study. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
42
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 24 publications
(33 reference statements)
6
42
1
Order By: Relevance
“…7,22,23 Despite revascularization, black race has been shown to affect patency of open and endovascular procedures. 4,8,9,28 The predilection for more aggressive atherosclerotic disease burden is further supported by our findings of the higher predicted 3-year amputation risk (5%) seen in black patients with DM and CKD/ESRD living in low-SES neighborhoods despite presenting early with claudication. In contrast, white patients with CLI and without the other risk factors have only a 7% predicted risk of limb loss over the same time.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…7,22,23 Despite revascularization, black race has been shown to affect patency of open and endovascular procedures. 4,8,9,28 The predilection for more aggressive atherosclerotic disease burden is further supported by our findings of the higher predicted 3-year amputation risk (5%) seen in black patients with DM and CKD/ESRD living in low-SES neighborhoods despite presenting early with claudication. In contrast, white patients with CLI and without the other risk factors have only a 7% predicted risk of limb loss over the same time.…”
Section: Discussionsupporting
confidence: 73%
“…Involvement of distal tibial vessels in PAD may preclude successful attempts at revascularization and increase the need for primary amputation 7, 22, 23. Despite revascularization, black race has been shown to affect patency of open and endovascular procedures 4, 8, 9, 28. The predilection for more aggressive atherosclerotic disease burden is further supported by our findings of the higher predicted 3‐year amputation risk (5%) seen in black patients with DM and CKD/ESRD living in low‐SES neighborhoods despite presenting early with claudication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the initiation of limb salvage programs, race and/or ethnic origins appear to drive some of the ongoing inadequate vascular medicine practices. Multiple studies have demonstrated that African-Americans, Hispanics and Asians comprise a disproportionately higher proportion of patients admitted for CLI and undergoing amputation, with a lower proportion undergoing revascularization [47,48]. With the overall minority population growth rate projected to be in the double digits in the coming decades [38], finding ways to deliver quality and cost-effective care especially to those currently predisposed to poorer outcomes is critical.…”
Section: Discussionmentioning
confidence: 99%